Efficacy of Abiraterone and Enzalutamide in Pre- and Postdocetaxel Castration-Resistant Prostate Cancer: A Trial-Level Meta-Analysis - Mike Fang; Mary Nakazawa; Emmanuel S. Antonarakis; Chun Li (Prostate Cancer)
We examined the comparative efficacies of first-line abiraterone and enzalutamide in pre- and postdocetaxel settings in castration-resistant prostate cancer (CRPC) through a trial level meta-analysis. A mixed method approach was applied to 19 unique studies containing 17 median overall survival (OS) estimates and 13 median radiographic progression-free survival (PFS) estimates. We employed a random-effects meta-analysis to compare efficacies of abiraterone and enzalutamide with respect to OS and PFS. In the predocetaxel setting, enzalutamide use was associated with an increase in median OS of 5.9 months (p<0.001), hazard ratio (HR) = 0.81, and an increase in median PFS of 8.3 months (p<0.001), HR = 0.47 compared to abiraterone. The advantage of enzalutamide improved after adjusting for baseline Gleason score to 19.5 months (p<0.001) and 14.6 months (p<0.001) in median OS and PFS, respectively. In the postdocetaxel setting, the advantage of enzalutamide use was nominally significant for median PFS (1.2 months p=0.02 without adjustment and 2.2 months and p=0.0007 after adjustment); there was no significant difference in median OS between the two agents. The results from this comprehensive meta-analysis suggest a survival advantage with the use of first-line enzalutamide over abiraterone in CRPC and highlight the need for prospective clinical trials.